As TIC como facilitadoras da aprendizagem significativa no ensino de física - Moraes, José Uibson Pereira (2012)
Starting from the reality of physics teaching today, and that this teaching is sometimes criticized, then it is thought to contribute to its improvement. With this motivation this research is intended to understand how the use of Information and Communication Technologies can contribute to the facilitation of The Meaningful Learning in the physics teaching. Therefore, it was used as theoretical support The Meaningful Learning of Ausubel in itself, The Education Theory of Novak and Gowin‟s Teaching and Learning Model. The methodology used was the action research. Data collection was obtained from the concept maps created by the students as well as notes and audio recordings. For quantitative analysis of the maps was used the score suggested by Gowin and Alvarez (2005), generating a score for each map. As for the qualitative analysis we used the classification levels of the Taxonomy Cañas et al. (2006). From these analyzes, we observed evidence of significant learning tied to the contribution of ICT.